Percutaneous Closure of a Large Ascending Aortic Pseudoaneurysm - Afonso Nogueira, M (2016)
Pseudoaneurysm of the ascending aorta is a rare complication, usually after thoracic surgery or trauma. Since surgical repair is associated with very high morbidity and mortality, percutaneous closure has been described as an alternative. In this regard, we present a case in which a symptomatic large pseudoaneurysm of the ascending aorta was treated percutaneously due to the high surgical risk. Despite the technical difficulties, this procedure had a good final result followed by clinical success.